A study of serum-ionized calcium in neonates with unconjugated hyperbilirubinemia on phototherapy - Pal, Swasti; Kalra, Braham Prakash; Kalra, Vinita (Indian Journal of Child Health, 2018)
Objectives: The objective is to study the occurrence of phototherapy-induced hypocalcemia in neonates with unconjugated hyperbilirubinemia and to compare the occurrence between pre-term and full-term neonates. Materials and Methods: The study was conducted in the Neonatology Unit of Department of Pediatrics, at a tertiary care teaching hospital for 12 months. A total of 230 full-term and pre-term neonates with jaundice were recruited. Of 230 neonates, 150 were given phototherapy (cases), while 80 did not receive phototherapy and were used as control. Serum-ionized calcium levels were measured at initiation, after 24 h and after 48 h, or at the end of phototherapy in the case duration of phototherapy was